Characterization of rhizospheric and non rhizospheric bacteria from arsenic contaminated soil - Mayda, Umma; Tasnim, Nazifa; Shilpi, Rasheda Yasmin (Jahangirnagar University Journal of Biological Sciences, 2019)
The rhizosphere soil has a large and various number of microorganisms especially the bacteria. This experiment was conducted at the department of Botany, Jahangirnagar University, Savar, to investigate the rhizospheric and non-rhizospheric bacteria from arsenic contaminated soil. Pteris vittata was treated with different concentrations of arsenic ranges from 5000 to 10000 ppm in the pot. The experimental result indicated that the negative correlation between arsenic concentration and rhizospheric soil bacteria. Highest number of bacteria (8.6×108 cfu/g) were found in rhizospheric soil (control), while lowest numbers of bacteria (4.0×107 cfu/g) were found in the non-rhizospheric soil with 10000 ppm arsenic. Thirty bacteria were isolated from rhizospheric and non-rhizospheric soil samples. Out of thirty samples Bacillus and Pseudomonas were selected on the basis of morphological and biochemical nature. The present study concluded that the arsenic has an adverse effect on the growth of rhizospheric soil bacteria. Jahangirnagar University J. Biol. Sci. 8(1): 9-15, 2019 (June)